DEVELOPING VIETNAMESE READING SKILLS FOR THE FIRST YEAR PUPIL - Tuyen, TTK (Proceeding of the International Conference on Arts and Humanities, 2024)
The purpose of the paper is to improve Vietnamese capacity of the first-year pupil through developing their Vietnamese reading skills (the author mentions the case of Vietnamese pupils and Chinese ethnicity pupils living in District 5, Ho Chi Minh City, Vietnam). To implement this paper, the author has conducted a study on the reading ability results of first-year pupils in Distric 5, Ho Chi Minh City, Vietnam, using a variety of research methods. Specifically, the author has used survey research to collect data from the participants, statistical analysis to analyze the data, and classification techniques to organize the data into categories or groups. Therefrom, the author would like to provide practical suggestions for improving their reading skills. These suggestions likely focus on teaching and learning methods that are suitable for the pupils’ current level of reading ability. The paper is not only meaningful in terms of academic, theoretical and practical aspects of teaching and learning activities to develop Vietnamese reading skills for first year pupils in Vietnam but also can be applied to teach reading skills in other languages of the world.